Tailoring Donor‐Acceptor Emitters to Minimise Localisation Induced Quenching of Thermally Activated Delayed Fluorescence. Issue 3 (7th December 2022) - Penfold, T. J.; Eng, J.
Abstract: By inverting the common structural motif of thermally activated delayed fluorescence (TADF) materials to a rigid donor core and multiple peripheral acceptors, it has been shown possible to achieve both a reverse intersystem crossing (rISC) rate > 62 1×10 7 s −1 and a unity photoluminescence quantum yield [Dos Santos et al . Adv. Sci. 5 (2018) 1700989]. However, the rISC rate in this motif is quenched by localisation of the excited state electronic structure which causes in‐equivalence between the peripheral acceptors. In this paper, we explore a series of related molecular targets which seek to reduce the effect of localisation on the rISC rates. This includes structures that contain donors exhibiting three‐fold or four‐fold symmetry and different degrees of steric hindrance around the donor‐acceptor bond with the objective of using steric hindrance to exert finer conformational control of the excited state dynamics to enhance functional properties. We demonstrate that a triazatruxene central donor is most effective for TADF owing to the energetic position of the locally excited state, while cyano‐benzonitriles are the most effective acceptors for reducing the effect of localisation on the electronic structure. These also push the emission into the blue region of the spectrum, opening the possibilities for this to be a pathway to develop efficient blue TADF emitters. Abstract : Designing Donor‐Acceptor TADF emitters to prevent excitation localisation due to symmetry breaking by studying the electronic structure along a series of donor and acceptor units.